2009
DOI: 10.1021/ja900616b
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Independent Binding Sites for Small-Molecule Inhibitors on the Oncoprotein c-Myc

Abstract: Deregulation of the c-Myc transcription factor is involved in many types of cancer, making this oncoprotein an attractive target for drug discovery. One approach to its inhibition has been to disrupt the dimeric complex formed between its basic helix-loop-helix leucine zipper (bHLHZip) domain and a similar domain on its dimerization partner, Max. As monomers, bHLHZip proteins are intrinsically disordered (ID). Previously we showed that two c-Myc-Max inhibitors, 10058-F4 and 10074-G5, bound to distinct ID regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
264
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(280 citation statements)
references
References 69 publications
5
264
3
1
Order By: Relevance
“…It is also possible that much of the decline in overall c-Myc levels simply reflects a secondary reduction in its synthesis as a result of cell cycle arrest in G 0 /G 1 (Yin et al, 2003). On the other hand, the invariant levels of Max probably reflect its much greater stability (t 1/2 ; Ͼ24 h), its lack of interaction with small molecules such as 10074-G5 or 10058-F4 (Wang et al, 2007;Follis et al, 2008;Hammoudeh et al, 2009), and its ability to interact with numerous other bHLH-ZIP factors (Baudino and Cleveland, 2001). 10074-G5 was nontoxic to Daudi tumor-bearing mice at 20 mg/kg i.v., its maximum soluble dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also possible that much of the decline in overall c-Myc levels simply reflects a secondary reduction in its synthesis as a result of cell cycle arrest in G 0 /G 1 (Yin et al, 2003). On the other hand, the invariant levels of Max probably reflect its much greater stability (t 1/2 ; Ͼ24 h), its lack of interaction with small molecules such as 10074-G5 or 10058-F4 (Wang et al, 2007;Follis et al, 2008;Hammoudeh et al, 2009), and its ability to interact with numerous other bHLH-ZIP factors (Baudino and Cleveland, 2001). 10074-G5 was nontoxic to Daudi tumor-bearing mice at 20 mg/kg i.v., its maximum soluble dose.…”
Section: Discussionmentioning
confidence: 99%
“…Because c-Myc must heterodimerize with its obligatory bHLH-ZIP partner Max to exhibit transcriptional activity (Walhout et al, 1997), several groups have designed smallmolecule inhibitors to interfere with this protein-protein dimerization and thereby inactivate c-Myc function (Berg et al, 2002;Yin et al, 2003;Kiessling et al, 2006;Xu et al, 2006;Wang et al, 2007;Hammoudeh et al, 2009;Shi et al, 2009). Berg et al (2002) showed that small molecules can interfere with c-Myc/Max dimerization and inhibit c-Mycdependent transformation of chicken embryo fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some small-molecule inhibitors were isolated to specifically inhibit Myc-Max dimerization and block the binding of Myc-Max to DNA without affecting other structure-like bHLH factor dimerization (165,166). By using Myc bHLH-Zip domain fragments, researchers also discovered local conformational changes and formation of hydrophobic cavities at the specific peptide sequences of the fragments upon binding with these small-molecule inhibitors (167). This makes it possible to design specific inhibitors simply through protein sequence analysis because the small-molecule binding sites have certain peptide sequence criteria.…”
Section: Perspective In Selectively Targeting Hey Proteins and Bhlh Fmentioning
confidence: 99%